Because

therefore
f(x) = (x-3)(2x² + 10x - 1) + k, where k = constant.
Because f(3) = 4, therefore k =4.
The polynomial is
f(x) = 2x³ + 10x² - x - 6x² - 30x + 3 + 4
= 2x³ + 4x² - 31x + 7
Answer: f(x) = 2x³ + 4x² - 31x + 7
Part A: The first thing you should do is to graph both lines. Notice that one is of positive slope and another of negative slope.
The solution of the inequation system is given by the shaded region. That is, all the points that are in the shaded region satisfy the system of inequations.
Part B: the point (-2, -2) is NOT included in the solution area (it is not in the shaded region.
Mathematically it is demonstrated by substituting inequalities and seeing that they are not satisfied
inequality 1 -2 <4 (-2) - 2
-2 <-10 (false)
inequality two -2> = - (5/2) (- 2) - 2
-2> = 3 (false).
She cycled 5 miles on the second day
Answer:

Step-by-step explanation:
Let sides of the triangle be 

Semi-perimeter (s) = 

Area of one tile 

So,
Area of 20 tiles 
Cost of polishing the floor at the rate of 2 rupees per sq.cm = 
Answer:
your answer is 100 <3 have a nice day
Step-by-step explanation: